ANALISIS PENGARUH PERTUMBUHAN JUMLAH PENDUDUK DAN PERTUMBUHAN EKONOMI (PDRB) TERHADAP TINGKAT KEMISKINAN DI KABUPATEN LOMBOK BARAT TAHUN 2015 – 2020 - Syahroni, Lalu Juniar; Rosita, Rosita (Nusantara Hasana Journal, 2022)
This study aims to determine the effect of population growth on the poverty level and economic growth (GRDP) on the poverty level in West Lombok Regency, as well as the influence of population growth and economic growth (GRDP) on the poverty level in West Lombok Regency simultaneously. This research was conducted in West Lombok Regency and the type of research used in this research is quantitative research with a descriptive approach. While the data used in this study is secondary data. The results of the study show that: 1) Population growth has a significant partial effect on the poverty level in West Lombok Regency; 2) Economic growth has a significant partial effect on the poverty level in West Lombok Regency; 3) Population growth and economic growth have a significant simultaneous effect on poverty levels in West Lombok Regency; 4) The variable of population growth affects the poverty level in West Lombok Regency is positive while economic growth has a negative effect on the poverty level in West Lombok Regency.